2017
DOI: 10.3314/mmj.16-00024
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of <I>Fusarium</I> Species Causing Invasive and Superficial Fusariosis in Japan

Abstract: In Japan, Fusarium species are known etiological agents of human fungal infection; however, there has been no report of a large-scale epidemiological study on the etiological agents of fusariosis. A total of 73 Fusarium isolates from patients with invasive fusariosis (IF, n= 36) or superficial fusariosis (SF, n= 37), which were obtained at hospitals located in 28 prefectures in Japan between 1998 and 2015, were used for this study. Fusarium isolates were identified using Fusarium- and Fusarium solani species c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 50 publications
(43 reference statements)
1
21
1
Order By: Relevance
“…19,31 FSSC has been further divided into several phylogenetic groups by phylogenetic tree analysis. Hassan et al reported that FSSC3 + 4 (also called Fusarium falciforme ) was predominantly isolated from keratitis, 6 whereas Muraosa et al 32 reported that FSSC3 + 4 was the most frequent isolate collected from patients with superficial fusariosis in humans, followed by FSSC5. In our present study, 10 keratitis-derived FSSC isolates were distributed among the FSSC5 (n = 5), FSSC3 + 4 (n = 4), and FSSC9 (n = 1) complexes (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…19,31 FSSC has been further divided into several phylogenetic groups by phylogenetic tree analysis. Hassan et al reported that FSSC3 + 4 (also called Fusarium falciforme ) was predominantly isolated from keratitis, 6 whereas Muraosa et al 32 reported that FSSC3 + 4 was the most frequent isolate collected from patients with superficial fusariosis in humans, followed by FSSC5. In our present study, 10 keratitis-derived FSSC isolates were distributed among the FSSC5 (n = 5), FSSC3 + 4 (n = 4), and FSSC9 (n = 1) complexes (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In Singapore, an outbreak of contact lens associated keratitis caused by FSSC species occurred in 2005 involving 66 patients (Jureen et al, 2008). An epidemiological study in Japan, from 1998 to 2015, found that FSSC species accounted for 72.6% of all fusariosis cases, of which 77.8% were invasive fusariosis (IF) (Muraosa et al, 2017). An analysis of a collection of environmental Fusarium isolates from the Malaysian highlands found that 66.1% of 1,449 isolates belonged to the FSSC (Manshor et al, 2012), highlighting their predominance in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Notes — Neocosmospora tonkinensis , previously known as FSSC 9, is known to include human pathogens, mostly isolated from corneal specimens (O’Donnell et al 2008, Muraosa et al 2017), as well as from animal infections (O’Donnell et al 2008, 2016). Short et al (2011) reported also the isolation of this species from water drains in the USA.…”
Section: Resultsmentioning
confidence: 99%